Frequency controlled drive of vibrating screens with unbalanced exciters: practical implementation and experimental results - Despotović, Željko V; Pavlović, Aleksandar I.; Vujić, Jovana (Proceedings, Electrical engineering institute "Nikola Tesla", 2023)
The paper presents a practically realized technical solution for frequency control of the AC power drive of vibrating sieves based on unbalanced vibration exciters. The operation of vibrating screen used in the industry for sieving and separating material fractions of different granulations is determined to a significant extent by the tilting angle of the vibrating sieve, its amplitude, the angle of attack of the excitation force and the frequency of oscillation. The frequency control of the vibrating sieves drive in this particular case made it possible to obtain the amplitude-frequency (AF) characteristic of the vibrating screen and based on it, the optimal operating frequency, which ensures the best separation of individual material fractions was determined. The solution was applied to two process lines in silos for de-ashing in the system of transport and separation of boiler slag from ash at the Thermal Power Plant "Nikola Tesla" B (TPP-B) in Obrenovac. The paper presents the key experimental results that were obtained during exploitation and testing of two implemented systems of regulated vibrating sieves.